"Eu tinha que enfrentar a estrada, embarcar em um casco": memorial de uma ribeirinha sonhadora - Santos, Glaciara Castro dos (Brasil, 2024)
This course completion memoir presents the recollections of a riverine student and aims to recall my personal, academic, and professional journey—from my first contact with student life to my current role as an effective education professional. The goal is to offer a reflective and in-depth perspective on the key life events, reflecting on the challenges and achievements that have shaped my teaching career. The memoir seeks to provide insights into classroom practices and the difficulties teachers face in pursuing qualifications. It also details the experiences gained during supervised internships in Early Childhood Education, Early Elementary Education, and Education Management. The internships aimed to contribute to my professional and personal growth, teaching me to be more patient, creative, and reflective—essential skills for handling various situations in the school environment. These practical experiences were crucial in consolidating my vocation and preparing me to face the job market with greater confidence and competence.